Urban sustainability challenges : Democracy and spatial injustices in Tunisia - Mahmoud, Abdesselem (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In this paper, the author addresses spatial injustices in Tunisia, and seeks to which extent social and territorial inequalities could hamper democracy. Many urban disparities and social anomies such as informal sector, terrorism, unemployment, and usustainable development process threaten the vulnerable democracy transition in Tunisia. The author described and analyzed urban planning process since independency to noawadays. He analyzed the successive economic development policy makings undertook by a mono-party Nation-State. The top down development policies implemented until nowadays entailed a big gap between coastal areas and inland. The former benefitted of its site across the sea shores and proximity to Tunis and former regime. Many factors fostered export industries and tourism activities. The latters were left behind due to their lack of resources and urban planning policy dominated by neo liberal capitalist development in favor of Tunis urban primacy and the littoral where concentrated most foreign and local investments. Urban disparities and inequalities in Tunisia join in a networked society where local and global actors play a key role in economic, social, and urban development process in Tunisia. Tunisian society is a subsystem within a global system (Wallerstein2012), and what is happening is not conjonctural, but it is due to global social movements (Sassen 2007 ; Castells 2012 ; Braudel, 1992 ; Amin, 2003). Terrorism, pollution, inequalities are not per se, but are the negative results of a a myriad of factors: economic, politics, cultural, emotional, aesthetics, social and urban morphologies. Many economic, social, and political actors intervened and interconnected in public and private arenas and triggered those anomies. Fair urban policies are expected to be achieved through a multilevel governance in order to implement the revolution objectives in Tunisia. Otherwise, a representative democracy only, won't fulfil the well-being expected by large Tunisian people. Sustainable urban governance requires a multi-scalar bottom-up and top-down policy-making. In Tunisia, after democratic transition success, the state should be revamped, and compensate its deficit. A sustainable urban planning implies a holistic policy framework involving private and public sectors, and civil society actors locally, regionally, and globally.